2018
DOI: 10.2116/analsci.18n001
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Analysis of Sialic Acid and Related Compound by Hydrophilic Interaction Liquid Chromatography Using Fluorescence Detection after Derivatization with DBD-PZ

Abstract: N-Acetylneuraminic acid (NANA) has been reported to react with hydrogen peroxide in vitro to produce 4-(acetylamino)-2,4-dideoxy-D-glycero-D-galacto-octonic acid (ADOA). We labeled NANA and ADOA with 4-(N,N-dimethylaminosulfonyl)-7-piperazino-2,1,3-benzoxadiazole (DBD-PZ) for simultaneous detection. The derivatized NANA and ADOA were separated using hydrophilic interaction liquid chromatography (HILIC) with fluorescence detection. The calibration curves of DBD-PZ-derivatized NANA and ADOA showed good linearity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The method is very specific and is also highly sensitive with studies reporting detection limits of sialic acids as low as 12 pg to as high as 0.46 ng. 76,78,80,81 One study reported the lower limit of detection as 0.3 mg but this appears to be due to the fact that this was the lowest size standard sample used by the authors and it appears that further validation with smaller sample quantities could be carried out. 79 DMB labelling has one disadvantage in that the derivatized sialic acids are not very stable for periods over 24 hours; they are only stable for hours at room temperature 82 and are sensitive to UV light.…”
Section: Derivatization Of Sialic Acid With Fluorescent Tagsmentioning
confidence: 98%
“…The method is very specific and is also highly sensitive with studies reporting detection limits of sialic acids as low as 12 pg to as high as 0.46 ng. 76,78,80,81 One study reported the lower limit of detection as 0.3 mg but this appears to be due to the fact that this was the lowest size standard sample used by the authors and it appears that further validation with smaller sample quantities could be carried out. 79 DMB labelling has one disadvantage in that the derivatized sialic acids are not very stable for periods over 24 hours; they are only stable for hours at room temperature 82 and are sensitive to UV light.…”
Section: Derivatization Of Sialic Acid With Fluorescent Tagsmentioning
confidence: 98%
“…A fluorescence derivatization method is generally popular as well as UV detection, and the sensitivity is comparable to MS detection. 16 In this study, we developed a highly sensitive quantification method using fluorescent derivatization of DAP using 2,3-naphthalenedialdehyde (NDA).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, various fluorescence derivatization reagents for typical functional groups such as amine, phenol, and carbonyl groups have been developed. [1][2][3][4][5][6][7][8][9] However, fluorescence derivatization can be difficult if the target molecules do not have typical functional groups that can be derivatized. Among such compounds that are difficult to derivatize, our research group have focused on aryl halides.…”
Section: Introductionmentioning
confidence: 99%